Trends in the Prevalence of Hypertensive Heart Disease in China From 1990 to 2019: A Joinpoint and Age–Period–Cohort Analysis - Xu, Dan; Hu, Jingcen; Wang, Shuyu; Chen, Lian (Frontiers in Public Health, 2022)
To the best of our knowledge, no comprehensive estimates of the descriptive epidemiology of and trends in hypertensive heart disease (HHD) in China have been reported. In this study, the temporal trends in the prevalence of HHD in China from 1990 to 2019 were estimated using an age–period–cohort model. Data related to HHD burden were collected from the Global Burden of Disease Study 2019. From 1990 to 2019, HHD prevalence in China showed decreasing trends in both sexes combined (average annual percentage change [AAPC]: −0.2%, 95% confidence interval [CI: −0.3% to −0.2%) and in males (AAPC: −0.5%, 95% CI: −0.5% to −0.4%), but significant increases in the age groups of 15–19, 20–24, …, and 60–64 years. The age effect analysis showed an increase in HHD prevalence from 50 to 94 years in both males and females, the period effect analysis showed a slight increase in HHD prevalence from 2009 to 2019 in females, and the cohort effect analysis showed a consistent decline in HHD prevalence from earlier to later birth cohorts in both males and females.